MAINTENANCE OF THE MAMANDA KUTAI MUSIC ECOSYSTEM SUSTAINABILITY OF ORIGINAL MUSIC IN THE MAMANDA PANJI BERSERI GROUP - Fikri Yassaar Arrazaq; Yofi Irvan Vivian; Zamrud Whidas Pratama (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2025)
The existence of traditional music in Mamanda Kutai theater art remains well-preserved by the Mamanda Panji Berseri group, as demonstrated by the consistent core patterns of piul and babon, as well as the relatively unchanged use of accompanying instruments. This preservation is particularly noteworthy given the significant developments observed in most other groups. This qualitative study aims to examine how the traditional Mamanda music ecosystem is systematically maintained by the Mamanda Panji Berseri group. The research employs a combination of desk and field methods, grounded in an ethnomusicological perspective. The findings indicate that various interrelated components within the ecosystem contribute to its sustainability, including learning systems, musicians and communities, contextual and structural frameworks, regulatory support and infrastructure, and the music industry. Furthermore, the study underscores that the role of the traditional Mamanda Kutai musical accompaniment ecosystem within the Mamanda Panji Berseri group still requires further optimization to enhance its long-term sustainability and broader impact.